Current situation and health risk assessment of neonicotinoids insecticides in urban indoor dust from Ha Noi, Viet Nam - Ho, Hoang Nguyen; Trinh, Ha Thu; Tran, Manh Duy; Duong, Hanh Thi; Dinh, Cuc Thi (Vietnam Journal of Science and Technology, 2023)
In the several decades, although neonicotinoids insecticides (typically imidacloprid and thiamethoxam) are widely used and account for 24 % of the total global pesticide production, they still have negative impacts on natural enemies such as kinds of bees as well as adversely affect human health. However, there are only a few studies evaluating the levels of imidacloprid and thiamethoxam in airborne environments including indoor dust. Therefore, the aim of this study was to investigate the distribution, concentration and health risk to human of imidacloprid and thiamethoxam in indoor dust samples collected from 6 inner districts of Hanoi. Imidacloprid was found in indoor dust samples at all samples with an average concentration of 0.079 µg/g (ranging from 0.028 to 0.216 µg/g, the detection frequency of 100 %). Meanwhile, the mean concentration of thiamethoxam was revealed lower than imidacloprid at 0.013 µg/g (ranging from 0.01 to 0.027 µg/g, the detection frequency of 60 %). In high-end exposure, based on the measured concentrations, daily intake doses (IDs) of imidacloprid and thiamethoxam were calculated to be 9.96 × 10-1 and 1.10 × 10-2 ng/kg-bw/day for adults, and 1.78 and 1.98 × 10-1 ng/kg-bw/day for children, respectively. The estimated values of hazard quotient (HQ) of imidacloprid and thiamethoxam were 1.75 × 10-6 and 9.20 × 10-7 ng/kg-bw/day for adults, and 3.13 × 10-5 and 1.65 × 10-5 ng/kg-bw/day for children, respectively. All HQ and HI values of the insecticides were less than 1 for both of adults and children, indicating the potential adverse effects to human health are negligible.